Management and automation of organic food deliveri services – a transportation model - Gdowska, K.; Jakubiak, M. (Energy and Automation, 2015)
In this paper an organic food delivery scheduling problem with time windows is presented. Described issue seems to be very important in the field of logistics in agriculture especially when organic food delivery to small shops, restaurants or customers’ houses are considered. In this kind of services the frequency and number of deliveries are significantly high and every producer and client should be visited in the defined time window, therefore there is a strong need for coordination of deliveries’ routes – every route begins with collecting goods from farms and subsequently, products are being delivered to customers. In this paper the organic food delivery scheduling problem is presented as a theoretical problem for which a mix integer programming model was developed. The model was employed for solving a small possible situation – computational experiment is described and results are reported. Moreover, directions for further research are suggested.